Students 'Critical Thinking Profile To Solve The Problem Of Analytical Geometry Viewed From Gender - Yuwono, Muhammad Ridlo; Udiyono, Udiyono; Maarif, Dimas Himawan; Sulistiana, Sulistiana (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This study aims to describe the profile of students' critical thinking in solving analytical geometry problems that are viewed from gender. This research is a qualitative study with case studies. Data analysis technique used are Miles and Huberman analysis, namely data reduction, data presentation, and presented conclusions. The results of this study are male students and female students who have met the standard eight intellectual critical thinking standards of analytical geometry, namely clarity, precision, accuracy, relevance, consistency, logical correctness, completeness, and fairness. On the intellectual standard of precision, male students were more careful in giving reasons for taking problem solving strategies to female students. At the intellectual standard of fairness, male students are able to provide two alternative solutions to problems, while female students only provide one initial solution to problem solving.